Postcolonial Indigenous Feminist Paradigm as a Strategy of Self-determination: A reflection on Papua Mimika Women in Matrilineal Tradition - Katmo, Els Tieneke Rieke (Jurnal Perempuan, 2016)
Feminism for some people in Indonesia viewed as a Western concept. They claimed that, It is a concept which is not rooted in Indonesia’s values. Even though there are several studies conducted to examine women’s issues in Indonesia, the result of those studies is insufficient to develop a body of knowledge or feminist theory of Indonesia. Historically, Indonesia in the past was a colonized nation which Dutch (Euro-Western) for some decades. This indicated that knowledge production process in Indonesia has been hegemonised by so-called Western knowledge. Decolonization and indigenization on research methodology is crucial to be able to establish an Indonesia’s feminist theory. The historical context of Indonesia as a colonized nation as well as cultural context impacted on various women’s issues in Indonesia including West Papua’s women. Therefore, providing spaces for multiple paradigm such a Postcolonial Indiegnous in a research is needed. The process of decolonization and indigenization in a research will provide a knowledge that based on indigenous perspectives on Indigenous purposes in the production of knowledge.